Effects of low water input on rice yield: Fe and Mn bioavailability in soil - Jahan, Md Sarwar; Yusop, Mohd Khanif; Syed Rastan, Syed Omar; Sinniah, Uma Rani (Universiti Putra Malaysia Press, 2013)
Soil fertility and water condition are the main concerns in rice production. In order to determine the effects of low water input on rice production and soil chemical properties, the Fe and Mn contents, and soil pH in soil were measured during rice cultivation. It was found that rice yield and yield parameters obtained were not significantly different under different water levels. Soil pH was moderately acidic to near neutral. Meanwhile, iron (II) in soil extract slowly increased throughout the rice growing period but it increased markedly after the water was drained off. Manganese availability significantly increased after flooding, but it decreased at a similar trend followed after that, followed by a stable level. In addition, weekly data showed no significant differences in Fe(II) and Mn in the soil extract of the different treatments. These results suggest that low water input does not affect rice production as well as soil pH and Fe(II) and Mn bioavailability in soil.